1974
DOI: 10.1128/jb.119.3.805-810.1974
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Spore Germination in Bacillus subtilis : Relationship to Inhibition of l -Alanine Metabolism

Abstract: The inhibitory effects of anthranilic acid esters (methyl anthranilate and N-methyl anthranilate) on the L-alanine-induced initiation of spore germination was examined in Bacillus subtilis 168. Methyl anthranilate irreversibly inhibited alanine initiation by a competitive mechanism. In its presence, the inhibition could be reversed only by the combined addition of D-glucose, D-fructose, and K+. Both L-alanine dehydrogenase and L-glutamate-pyruvate transaminase, enzymes which catalyze the first reaction in L-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…These three acids (plus oxaloacetate, which was measured as pyruvate) were selected for analysis because they are convenient intermediates of the two halves of the tricarboxylic acid cycle and of the lower half of glycolysis. Pyruvate is also the product of alanine dehydrogenase (EC 1.4.1.1), which has often been suggested to be the site of action of L-alanine as a germinant, and a-oxoglutarate is necessary for the action of the transaminases, which have been implicated in spore germination (Prasad, 1974). Fig.…”
Section: Concentrations Ofmalate A-oxoglutarate Andpyruvate During Gmentioning
confidence: 99%
See 2 more Smart Citations
“…These three acids (plus oxaloacetate, which was measured as pyruvate) were selected for analysis because they are convenient intermediates of the two halves of the tricarboxylic acid cycle and of the lower half of glycolysis. Pyruvate is also the product of alanine dehydrogenase (EC 1.4.1.1), which has often been suggested to be the site of action of L-alanine as a germinant, and a-oxoglutarate is necessary for the action of the transaminases, which have been implicated in spore germination (Prasad, 1974). Fig.…”
Section: Concentrations Ofmalate A-oxoglutarate Andpyruvate During Gmentioning
confidence: 99%
“…intermediates of the tricarboxylic acid cycle could the extended also not be found, and the absence of a-oxoglutarate from the dormant spore makes a role for glutamateexperiments. pyruvate transaminase (EC 2.6.1.2) in alanineted until 4min induced germination (Prasad, 1974) unlikely. No it is unlikely pyruvate could be detected (produced from alanine important in by alanine dehydrogenase), suggesting that the production of pyruvate by spores inhibited from germination by an inhibitor of pyruvate metabolism (Halvorson & Church, 1957) may be due to the presence ofthe inhibitor rather than to a germinationrelated event.…”
Section: ) That Mightmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially acetate formation is an energy producing step 36 that is beneficial for germination and outgrowth. It has been observed that pyruvate formed via Ald may be converted to fructose-6-phosphate via gluconeogenesis thus fuelling cellular energy generation processes 37 . Protein YoeB (IseA), an autolysis activation modulator 38,39 may serve as a controller restricting cell division ahead of time.…”
Section: Discussionmentioning
confidence: 99%
“…Realization that the selective inhibition of specific stages during germination is the best approach to prevent this spoilage has led to the search for metabolic inhibitors. The inhibitory compounds reported to date belong to the following classes: long-chain fatty acids (3), analogues of amino acids (2,6), purines and pyrmidines (2,9), metal chelators and ions (7), and antibiotics (5).…”
mentioning
confidence: 99%